Rancang Sangkar Burung Pintar Berbasis IoT - Tutuko, Aryo Bagus Kusumadewa; Hidayahtullah, Maulana Syarief; Hamkah, Nafarul; Nilofar, Rafli Alfian; Pramudhita, Agung Nugroho (Universitas Merdeka Malang, 2023)
Raising birds for hobby and breeding is currently trending in the community. With the general business of the public, a common challenge faced by bird enthusiasts is the process of caring for birds, especially providing timely and accurate feeding and watering. To address this issue, research has been conducted to create a smart bird cage. The smart bird cage is designed to automatically provide food and water with remote control via mobile internet. This research applies modules such as ESP8266-01, servo motor, Relay 2 module, water level sensor, mini water pump, ultrasonic sensor, and the Blynk application that can be integrated as a control service using IoT. The result of this research is the specification of the cage for providing food and water that can be controlled automatically with specific measurements so that the feeding and watering patterns can be more organized.